1991
DOI: 10.1111/j.1365-2265.1991.tb03493.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation and suppression of intact parathyroid hormone (PTH1–84) in normal subjects and hyperparathyroid patients

Abstract: The wide range of responses to stimulation and suppression tests and the correlation between these responses in hyperparathyroid patients indicate various degrees of autonomy. As the response to these tests is less marked in patients than in controls and both groups still overlap, these tests are not useful for the diagnosis of primary hyperparathyroidism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
3

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 15 publications
2
15
0
3
Order By: Relevance
“…parathyroid adenoma or hyperplasia) parathyroid cells (9)(10)(11)15), and both cell types reduce their PTH secretion in response to a rise in serum calcium either in vitro (30) or in vivo (11,22,(30)(31)(32)(33). However, cells from patients with PHP appear less sensitive to calcium-loading suppression than normal parathyroid cells (30,32,34,35). On this basis calcium-loading suppression tests were proposed as tools for the diagnosis of PHP with various modalities (oral or i.v.…”
Section: Discussionmentioning
confidence: 99%
“…parathyroid adenoma or hyperplasia) parathyroid cells (9)(10)(11)15), and both cell types reduce their PTH secretion in response to a rise in serum calcium either in vitro (30) or in vivo (11,22,(30)(31)(32)(33). However, cells from patients with PHP appear less sensitive to calcium-loading suppression than normal parathyroid cells (30,32,34,35). On this basis calcium-loading suppression tests were proposed as tools for the diagnosis of PHP with various modalities (oral or i.v.…”
Section: Discussionmentioning
confidence: 99%
“…An oral calcium supplement of 1000 mg decreases serum PTH within one hour [19]. Calcium supplementation can reduce serum PTH during 24 h [20].…”
Section: The Influence Of Calcium Intake On the Required Serum 25(oh)dmentioning
confidence: 99%
“…In primary hyperparathyroidism approximately half of patients apparently have essentially autonomous parathyroid function, while the others retain the capacity for suppression despite impaired sensitivity or a set-point abnormality [14]. Actually it has been reported that intravenous calcium infusion inhibits PTH secretion from the adenoma via CaSR activation [15,16]. Many reports have stated that hypercalcemia due to parathyroid adenomas is responsive to calcimimetics, indicating this regulation of PTH through the CaCaSR signaling pathway [17].…”
Section: Discussionmentioning
confidence: 99%
“…He was referred to an endocrinologist because of hypercalcemia (corrected calcium (cCa) 15.0 mg/dl) that happened to be detected during an outpatient examination to rule out malignancy. He was also found to have hypophosphatemia (1.7 mg/dl), elevated iPTH level (220 pg/ml), elevated 1,25(OH)2 vitamin D level (76.4 pg/ml), and mild renal insufficiency (s-Cr 1.59 mg/dl), and hospital admission was planned for further examinations.…”
Section: Case Reportmentioning
confidence: 99%